Busting of myths and misconceptions about breast feeding during COVID-19 pandemic and its societal importance: a brisk review - Swain, Dharitri; Parida, Swayam Pragyan; Das, Hrushikesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
COVID-19 considered as a public health emergency of International concern and thus a pandemic with the explosive increase rate of infection worldwide and at the same time, the healthcare system is struggling for survival and the government is striving to regain the trust of the population. According to the WHO, mothers with COVID-19 or suspected COVID-19 can breastfeed their babies as long as they take appropriate precautions. Although creating awareness and providing adequate information to the mother and general public about breastfeeding benefits, still people believe in several myths and misconceptions due to fear of the COVID-19 pandemic. These personal beliefs, misconceptions, myths, and cultural practices can have a negative impact on breastfeeding which may discourage breastfeeding practice among women. This brisk review intends to compile the latest available evidence about myths, cultural practices preventing breastfeeding during COVID 19 pandemic. We searched works of literature related to breast feeding during COVID -19 published between December 2019, and August 2020, in website archive of Ministry of Health and Family Welfare, World Health Organization (WHO), Centre for Diseases Control and Prevention (CDC), United Nations Children’s Fund (UNICE), journal repositories such as Google Scholar, Pub Med, Science Direct, newspaper article etc. We identified 30 studies that met the search criteria for inclusion in the review. The evidence presented here related to the common believes may alleviate the potential source of anxiety related to COVID-19 breast feeding issues who are still dependant on the societal misconception not the evidence.